Pengaruh Profesionalisme, Tekanan Waktu, dan Locus of Control terhadap Kualitas Audit di Inspektorat Kabupaten Cirebon: Studi Empiris - Hasyimiyyah, Aqilah; Lestari, Widyani Ayu; Dewi, Dessy Kumala (Politeknik Negeri Ambon, 2024)
This study examines the factors that affect audit quality in the Inspectorate of Cirebon Regency, focusing on the role of auditor professionalism, time pressure, and locus of control. Using a quantitative approach and a census sampling technique, the study surveyed 30 auditors, with a structured questionnaire consisting of 24 Likert-scale questions. The results reveal that professionalism does not significantly influence audit quality (H1 rejected), while time pressure has a significant negative effect on audit quality (H2 accepted). Additionally, locus of control was found to have no significant impact on audit quality (H3 rejected). The coefficient of determination (R²) is 0.386, indicating that professionalism, time pressure, and locus of control collectively explain 38.6% of the variation in audit quality, while other unexamined variables account for 61.4%. These findings highlight the need for improving time management and auditor professionalism to enhance audit outcomes.